Antenna Arrays Applications to Modern Wireless and Space-Born Systems - Al-Rizzo, Hussain M.; Kunju, Nijas; Tariq, Sulaiman; Klautau, Aldebaro (IntechOpen, 2022)
This book provides a comprehensive overview of antenna arrays and their applications in wireless communication systems. It presents modern studies of reconfigurable antenna arrays, radar antenna arrays, radiation pattern analysis, and optimization and coverage determination for antenna arrays. It also explores current methods of antenna array design, characterization, and evolution.